Students’ Perceptions on the Use of Online Quiz Platforms in English Literature Department UINSA - Salsabila, Nadiah; Kartika Fi’aunillah, Tristy (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Online media’s popularity in English teaching has been exceptionally vast in recent years. One of the challenges ESL teachers and lecturers face is keeping the students’ motivation and preventing the boredom in the class, which is feasible through online quiz platforms. This study examined what students think of Quizizz and Kahoot as online quiz platforms and how they affect their understanding in learning. A total of 50 respondents were gathered in this study, consisting of students in the second semester. The data were collected using survey questionnaires, observation, and interviews. The results reveal that the quiz platforms have boosted the students’ motivation and improved their perceptions as well as comprehension in learning. The gamified nature of the platforms adds an element of fun that contributes to a positive learning experience. Moreover, the platforms’ features allow the lecturers to give instant feedback that reinforces students’ comprehension.